Association of ABO blood group and age with COVID-19 positive test - Nalbant,Ahmet (2021)
ABSTRACT OBJECTIVE: The aim of this study is to evaluate the relation between the coronavirus (SARS-CoV-2) disease (COVID-19) and blood groups and the Rh factor. METHOD: A total of 313 patients hospitalized in the Internal Medicine clinic, at the intensive care unit (ICU) were included in the study. The cases were divided into two groups: those who were COVID-19 positive and those negative, detected with real-time reverse transcription polymerase chain reaction testing. The demographic, clinical, ABO blood groups, and Rh factor data of the cases were obtained from the hospital records retrospectively. RESULTS: The mean age of COVID-19 positive (+) cases was 57.74±16 years and of COVID-19 negative (-) cases, 66.41±15 years. The difference was significant (p<0.001); there was no difference between the two groups in terms of sex (p=0.634). When age was categorically separated in COVID-19 (+) cases, χ2 was extremely significant. Among the ABO blood groups of COVID-19 (+) and (-) cases, χ2 was 4.975 (p=0.174). In the logistic regression, it was 4.1 (p=0.011) in the O blood group. COVID-19 positive test was determined as 13, 4, and 4 times higher in the 31–40, 41–50, and 51–60 age groups, respectively (p=0.001, p=0.010, p=0.003). CONCLUSION: The incidence of COVID-19 has increased in the younger population and in the O blood group. Our findings support that, in this population, the ABO blood groups can contribute to the early detection of COVID-19.